A study on structural performance of deconstructable bolted shear connectors in composite beams. (February 2021) - Ataei, Abdolreza; Zeynalian, Mehran
Abstract: An experimental study according to EC4 on deconstructable steel-concrete composite bolted shear connectors is carried out to investigate the effect of various bolt size, concrete strength, bolt strength and clearance size between the precast concrete slab and bolt on the static behaviour of this type of composite connection. Shear load capacity for the first bearing, average major slip at the first bearing, maximum shear load capacity per bolt, slip corresponding to the maximum shear load capacity, maximum average slip between the precast concrete slab and steel beam and failure modes are assessed. A total of 12 composite specimens were tested according to EC4 with different parameters using deconstrcutable bolted shear connectors. In addition, two steel-concrete composite connection specimens using welded headed stud shear connectors were tested as control specimens to determine the influence of prefabricated concrete panels and deconstructable friction-grip bolted shear connectors on the performance of the steel-concrete composite connection. The experimental results show that deconstrcutable steel-concrete composite bolted shear connectors have completely different behaviour compared to welded headed stud shear connectors. Furthermore, a 3D finite element model of the steel-concrete composite connection having precast concrete slabs and deconstructable bolted shear connectors was performed. Numerical model was verified against experimental results, and was shown to accurately simulate their observed structural behaviour.